Ex situ conservation of Myrtaceae : a response to myrtle rust in the Pacific Region : a thesis presented in partial fulfilment of the requirements for the degree of Doctoral of Philosophy (PhD) in Plant Science at Massey University, Palmerston North, New Zealand - van der Walt, Karin (Massey University, 2022)
Many Myrtaceae species are threatened with extinction due to the arrival of myrtle rust (Austropuccinia psidii) in the Pacific Region. Ex situ conservation, in particular seed banking and cryopreservation, requires knowledge of the seed biology of the species to develop optimum long-term seed storage protocols. This information is limited for many New Zealand species. This study investigated ex situ conservation options for five critically endangered Myrtaceae species; Lophomyrtus bullata (ramarama), Lophomyrtus obcordata (rōhuto), Neomyrtus pedunculata (rōhuto), Metrosideros bartlettii (rātā moehau) and Syzygium maire (swamp maire). Less than 14 individuals of M. bartlettii remain in the wild. Using six trees in cultivation, the breeding system was found to be self-incompatible, thus an unrelated pollen donor is required to produce viable seed. With many trees in cultivation closely related, hand-pollination is an essential management tool. For hand-pollination to be successful, viable pollen must be available at the precise time. This study compared viability of pollen sourced from different trees and for the same tree over two years. Pollen germination protocols, which can be used to quantify pollen viability, were developed while short- and medium- term pollen storage methods are described. The seed morphology, seed germination requirements, seed desiccation tolerance, the combined impact of desiccation and freezing, and storability at 5°C, -18°C and -196°C of Lophomyrtus bullata, L. obcordata and Neomyrtus pedunculata were investigated. All three species were found to have intermediate seed storage physiology. L. bullata and N. pedunculata were sensitive to desiccation (~15% equilibrated relative humidity). Lophomyrtus bullata was also found to be freezing sensitive, while two of the three L. obcordata seed lots tested also displayed significant seed viability loss following storage at -18°C. Differential Scanning Calorimetry (DSC) analysis revealed that lipid crystallization in all three species occurred between -18°C and -52°C, and it is postulated that the lipids are in a metastable state when stored under conventional seed banking temperatures (c. -18°C). It is recommended that seeds of these three species are best stored outside of their lipid metastable temperature ranges. Syzygium maire seed and embryos are highly recalcitrant. This study investigated the oxidative stress, thermal properties, and ultrastructure of zygotic embryo axes (EAs) desiccated to various moisture contents (MC). Using rapid desiccation, moisture content in EAs were lowered to ~0.3 g/g resulting in ~50% of the EAs surviving. Exposure to liquid nitrogen was however fatal irrespective of the moisture contents tested. The enzymatic antioxidants superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPOX) significantly decreased following desiccation, while there was a corresponding 7-fold increase in the production of protein carbonyls and lipid peroxides. Exogenous application of ascorbic acid (AsA) increased antioxidant activity in desiccated EAs but not by a significant amount. The decrease in antioxidant activity following desiccation as well as the presence of melt enthalpies observed on the DSC thermograms, confirmed that for cryopreservation of S. maire EAs to be successful, rapid desiccation needs to be combined with cryoprotection. Plant Vitrification Solution 2 (PVS2) moderated the thermal behaviour in S. maire EAs with the novel droplet vacuum infiltration vitrification (DVIV) significantly improving embryo survival and plantlet development compared to droplet vitrification (DV). Neither method however resulted in embryo survival following exposure to liquid nitrogen. Longer incubation times using DVIV combined with physical desiccation should be investigated for the cryopreservation of S. maire. The four fleshy New Zealand Myrtaceae species, Lophomyrtus bullata, L. obcordata, Neomyrtus pedunculata and Syzygium maire were not amenable to conventional seed banking. Seed from Lophomyrtus and Neomyrtus displayed intermediate storage physiology due to sensitivity to desiccation and storage at -18°C, while S. maire seeds were highly recalcitrant. Cryopreservation, including the use of cryoprotectants and optimisation of cooling/warming rates, should be investigated for Lophomyrtus and Neomyrtus. Syzygium maire embryos did not regenerate successfully following any of the cryopreservation methods tested in this study (rapid desiccation, encapsulation-dehydration, cryoprotection). Further optimisation of cryopreservation methods for S. maire should be investigated. This includes application of exogenous antioxidants, increased cooling/warming rates, longer PVS2 incubation times and combining DVIV and rapid desiccation.
Keywords: Myrtaceae; Conservation; New Zealand; Germplasm resources; Endangered plants; Plant conservation; 310806 Plant physiology; 410401 Conservation and biodiversity